Diary of a Disaster : British Aid to Greece, 1940-1941 - Higham, Robin, 1925-2015 (Book collections on Project MUSE., 1986)
On October 28, 1940, the Italian army under Benito Mussolini invaded Greece. The British had insisted on guaranteeing Greek and Turkish neutrality, despite the fact that Greece was never more than a limited campaign in an unlimited war as far as they were concerned. The British, however, were never quite sure that Greece was not their last foothold in Europe, and they harbored dreams of holding on to this last bastion of civilization and of protecting it with a diplomatic and military alliance -- a Balkan bloc. These dreams bore little relation to military and economic realities, and so the st.